A Warning Model of Centralized Credit Default in Commercial Banks - Liu, Xinyu; Yin, Zhe (International Journal of Emerging Trends in Social Sciences, 2018)
The development and operation of commercial Banks have a great relationship with risks, which can not only bring profits to Banks, but also bring about crisis. Among them, credit risk is the most important risk. The traditional evaluation model is aimed at individual default risk, however, due to the changes of macroeconomic and between individuals infectious, centralized credit default has also become a topic worthy of thinking deeply. One of the most important factors leading to the concentration of credit default is the infectivity of individuals. In this paper, the author mainly discusses the effect of the infection of individuals on the centralized credit default, and constructs a new warning model with the impact model and establishes a reasonable warning field. When the time interval of two consecutive defaults is less than that of the warning region, the bank should take preventive measures immediately.